The Evaluation of Neuroprotective Effect of Nigella sativa Linn Seed Using Zebrafish Model - Sudha , S.; Chitra , B.; Nisha , S. Arif (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Naturally occurring materials that can serve as preservatives in foodstuffs are substances found in their composition. Nigella sativa Linn, a member of the Ranunculaceae family, is a widely recognized medicinal herb with global usage. For centuries, N. sativa L., seeds have been employed to address various ailments and health issues. In behavioral research, the bioactive compound derived from N. sativa L., namely Kaempferol 3-(2-galloyl-alpha-L-arabinopyranoside), has gained significant attention. The escalating prevalence of Alzheimer's disease among elderly individuals worldwide necessitates exploration beyond traditional mammalian and rodent models. This has led to the adoption of zebrafish (Danio rerio) as a unique model organism in biomedical research, behavior analysis and human disorders. Experiments involving scopolamine-induced T-maze, escape, place preference and bite tests have strongly suggested that behavior in zebrafish is governed by conserved regulatory processes. The results of the behavior tests demonstrated that N. sativa L., enhances learning and memory, which was otherwise affected by scopolamine treatment. Notably, a thorough analysis of histoarchitecture revealed no adverse effects of Kaempferol 3-(2-galloyl-alpha-L-arabinopyranoside), which might be a promising therapeutic option for such a multi-factorial Alzheimer's disease.